Predicting the Current and Future Habitat Distribution for an Important Fruit Pest, Grapholita dimorpha Komai (Lepidoptera: Tortricidae), Using an Optimized MaxEnt Model - Li Huang; Shichao Zuo; Yiqi Huo; Lizong Hu; Zhengbing Wang; Jiahui Zhang; Jin Liu; Weili Ding; Keshi Ma; Mingsheng Yang (Insects)
The Grapholita dimorpha is one of the significant borer pests that primarily damage plum, pear, and apple trees, often resulting in substantial economic losses in fruit production. However, the potential distribution range of this economically important pest remains poorly understood. In this study, we simulated an optimized maximum entropy (MaxEnt) model to predict the spatiotemporal distribution pattern of G. dimorpha and identified its underlying driving factors. The results indicate that suitable habitats, under current bioclimatic conditions, are mainly distributed in eastern China, northeastern China, Korea, and Japan, covering a total of 273.5 × 104 km2. The highly suitable habitats are primarily located in Korea and parts of central Japan, with a total area of 19.8 × 104 km2. In future projections, the suitable area is expected to increase by 17.74% to 62.10%, and the suitable habitats are predicted to shift northward overall. In particular, there are more highly suitable habitats for G. dimorpha in China and Japan compared to their predominance in Korea under current climatic conditions. The bio9 and bio18 contribute 51.9% and 20.7% to the modeling, respectively, indicating that the distribution of G. dimorpha may be shaped mainly by the mean temperature of the driest quarter and precipitation of the warmest quarter. In summary, the distribution range predicted, particularly for regions with highly suitable habitats, poses a high risk of G. dimorpha outbreaks, emphasizing the priority of pest monitoring and management. Furthermore, the key bioclimatic variables identified could also provide crucial reference for pest monitoring.